TINJAUAN YURIDIS TERHADAP PELAKSANAAN PENGANGKATAN ANAK PASCA BERLAKUNYA UNDANG-UNDANG NOMOR 3 TAHUN 2006 - Bastoni, Mohammad (2011)
This research focused at problem "Yuridis Review to Execution of Lifting of Child of Post Implementation of Number 3, 2006. By taking specification of discussion about First, how penal Islam concept of child lifting. Second, how lifting legal consequences of child of through religion justice. Third, needs lifting record-keeping of child of in office is note of Sipil based on stipulating religion justice. Research applies approach yuridis-normatif. Its the data collecting technique for document study through data is written by utilizing deductive conclusion, data which collected analyzed in kualitatif deskriptif. Result from this research is as follows: Firstly, based on Islam concept, lifting a child may not break lineage between the child with old fellow contains it. This thing later relates to heir system and marriage. In marriage for example, becoming lineage sponsor priority for daughter is father contains his own. In heir, foster child is not be including heir. Lifting of child of based on Islam law is lifting of child coming from Al-Qur'an and sunnah and result ijtihad applied in Indonesia formulated in so many idea product of Islamic law, good in the form of fikih, religious advices, justice decision, and also law and regulation, included in of Kompilasi Hukum Islam (KHI). Second, borns it invitors Nomor 3, 2006 about reformation to invitors number 7, 1989 about religion court has brought basic change to religion court authority. One of the change is lifting case of child of is including new authority of justice of religion as determined in clarification of section 49 numeral 20. The affirmative, in one sides shows existence of confession from country to lifting institute existence of child of in perspective punished Islam. On the other side at the time of the same parries doubtfulness of moslem public and the religion court law practitioners to exploit the institute. Islamic law marks that contractual terms between foster parents with limited foster child as relation between parenthood with child of mothering extended, and not at all creates the relation of lineage. Legal consequences from lifting of child of in Islam creation relation of love and darling and the relation of responsibility as fellow being. For absense of the relation of lineage, hence other law consequence is between foster parents with foster child must take care of mahram, dank arena there is no the relation of lineage, hence both can pass off marriage. Very necessary for the parties which have interest written its the foster child to in note of civil